Protective properties of water-ethanol extract Hericium erinaceus in combined chemical-radiation injury in experiment - Veyalkina, Nataliya N.; Kadukova, Alena M.; Nadyrov, Eldar A.; Shakhouskaya, Volha V.; Trukhanavets, Vyacheslav V.; Dvornik, Yuliya V.; Tsukanova, Alena V.; Miadzvedzeva, Alena A. (Journal of the Belarusian State University. Ecology, 2021)
In the clinical practice of treating liver diseases, drugs are often used - hepatoprotectors, the action of which is aimed at reducing the activity of inflammatory processes and increasing the liver’s resistance to pathological influences. Funds of natural origin are promising hepatoprotectors. The fruit bodies of H. erinaceus are rich in proteins, fats, cellulose, polysaccharides and various amino acids, which determines their biological activity. The aim of this work was to study the protective properties of a water-ethanol extract of H. erinaceus fruit bodies obtained by artificial cultivation in an experiment on Wistar rats, which were subjected to a combined effect of carbon tetrachloride and total single γ-irradiation at a dose of 3 Gy. After chemical and radiation exposure, the animals received a water-ethanol extract of H. erinaceus at doses of 0.5, 1.5 and 4.5 ml/kg and a comparison drug “Hofitol” at a dose of 1.5 ml/kg daily for a month. In the blood of rats receiving an aqueous-alcoholic extract of H. erinaceus fruiting bodies at doses of 1.5, and 4.5 ml/kg, the activity of alanineaminotransferase and aspartateaminotransferase was restored. It was found that the studied extract promotes restoration of the histological structure of rat liver, which is characterized by a decrease in the severity of fatty degeneration of hepatocytes and restoration of the structure of the liver lobules.